Electrodeposition of polypyrrole on carbon nanotube-coated cotton fabrics for all-solid flexible supercapacitor electrodes. Issue 16 (2nd February 2016) - Huang, Sanqing; Chen, Peishan; Lin, Wenzhen; Lyu, Siwei; Chen, Guangda; Yin, Xinyi; Chen, Wenxing
Abstract : Polypyrrole and carbon nanotube were attached on cotton fabrics as electrodes to prepare all-solid, flexible supercapacitors. Abstract : The increasing trend for portable and wearable electronic products requires the development of portable and flexible energy-storage systems, such as flexible supercapacitors. We have attached polypyrrole and carbon nanotubes to cotton fabrics as electrodes to prepare all-solid, flexible supercapacitors. Since the substrate is cotton, the supercapacitor is comfortable when worn and when in contact with the skin. Electrochemical measurements showed that the supercapacitor had a specific capacitance of 201.99 F g −1 at 1.8 A g −1 . Its high capacitance, stability, flexibility, low-cost, and wearable comfort make this supercapacitor a good candidate as an energy-storage device for portable and wearable electronic products.